MORPHOLOGICAL FEATURES OF THE POTTERYLEXICON IN ENGLISH AND UZBEK LANGUAGES - Nuraliyev Ilyos Ismoilovich (International Engineering Journal For Research & Development, 2020)
This article provides a statistical analysis of the morphological method, which is one of the sources of enrichment of English and Uzbek ceramic lexicon. It also studies the use of affixes in both languages and their specific features